Physico-Chemical study of fresh water body of Garhwa Johar, Fatehpur, Sikar, Rajasthan (Journal of Advances and Scholarly Researches in Allied Education, 2025)
This study examines the monthly variations in the physico-chemical characteristics of Garhwa Johar, a water body in Fatehpur, Sikar, Rajasthan, India, from July 2023 to June 2024. Seventeen parameters, including air and water temperature, pH, turbidity, specific conductivity, dissolved oxygen (DO), total dissolved solids (TDS), carbonate, bicarbonate alkalinity, total alkalinity, biochemical oxygen demand (BOD), hardness, calcium, magnesium, chloride, fluoride, and nitrate, were analyzed to assess water quality dynamics. The results reveal significant seasonal fluctuations influenced by the semi-arid climate of Sikar, monsoon patterns, and anthropogenic activities such as agricultural runoff. These findings highlight the need for continuous monitoring to ensure the ecological health and sustainability of Garhwa Johar in a water-scarce region like Rajasthan.